Corrosion Monitoring System On Concrete Using Concrete Resistivity Test Based On The Internet Of Things - Dinda Karina; Herry Sufyan Hadi; Putri Yeni Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Reinforced concrete, which is currently widely used as the main material for the establishment of a building infrastructure, consists of cement and iron and steel, which have the potential for corrosion by the active and passive layers of concrete. So with the high potential for corrosion that causes cracks to break and the building collapses, it is necessary to monitor the corrosion rate which can be used as a preventive measure for corrosion in concrete structures. Corrosion that occurs is also greatly influenced by the permeability and resistance of the concrete which causes the gaps of other elements to enter the concrete structure and accelerates the corrosion rate of the concrete. This study designed a corrosion Monitoring system in concrete with an IoT-based concrete resistivity test by injecting the concrete through an electric current which can be monitored with the Blynk application according to the area of the concrete.